The 2014 ACM International Conference on Measurement and Modeling of Computer Systems 2014
DOI: 10.1145/2591971.2592009
|View full text |Cite
|
Sign up to set email alerts
|

Non-intrusive, out-of-band and out-of-the-box systems monitoring in the cloud

Abstract: The dramatic proliferation of virtual machines (VMs) in datacenters and the highly-dynamic and transient nature of VM provisioning has revolutionized datacenter operations. However, the management of these environments is still carried out using re-purposed versions of traditional agents, originally developed for managing physical systems, or most recently via newer virtualization-aware alternatives that require guest cooperation and accessibility. We show that these existing approaches are a poor match for mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Study [12] observed that offloading low CPU utilizing (i.e., monitoring) tasks from the node's operating system to the BMC reduced the power consumption by a factor of 2.6. There is an increasing trend to perform system monitoring using OOB mechanisms [13,14].…”
Section: Saving Significant Energymentioning
confidence: 99%
“…Study [12] observed that offloading low CPU utilizing (i.e., monitoring) tasks from the node's operating system to the BMC reduced the power consumption by a factor of 2.6. There is an increasing trend to perform system monitoring using OOB mechanisms [13,14].…”
Section: Saving Significant Energymentioning
confidence: 99%
“…A monitoring approach for cloud-hosted virtual machines is presented in [21]. Monitoring is performed outside the VM using a virtual machine introspection (VMI) interface to read the VM memory and disk images.…”
Section: B Related Workmentioning
confidence: 99%
“…Cloud-based analytics are applied to the extracted data to find information of interest, such as malware identification. This can be a powerful tool to implement out-of-band monitoring and analysis for cloudhosted VMs, where even compromised or failed VM instances can be monitored and analysed with high-confidence [21]. Approaches such as VMI can be used as a security probe, and our SE based approaches to achieve trust in it.…”
Section: B Related Workmentioning
confidence: 99%
See 1 more Smart Citation